Analysis of influencing factors of passes in the chinese super league - Zeng, Y.; Zhang, H. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background In football matches, passing is an important means of organizing attacks, creating shots, changing tactics, and achieving tactical objectives and is a frequently used technique. The purpose of the study was to explore the relevant factors that affect passes in the Chinese Super League (CSL) in different game contexts.